Connection of Body Mass Index (BMI) Against Angle Shape Arch Pedis Longitudinal on Students of The Faculty of Medicine, Universitas Wijaya Kusuma Surabaya - Ayly Soekanto; Teofilus Dani Prasetyoadi; Hardiyono Hardiyono (Universitas Wijaya Kusuma Surabaya, 2023)
Physical growth during adolescence will occur at more than 20% of total height growth, and 50% of bone mass has also been achieved during this period. Body Mass Index (BMI) to control normal body weight is achieved by adjusting body height. BMI can be used to interpret the possibility that the person is at risk of developing risk of weight-related diseases. The human feet are the most important part of supporting our body and can be correlated with body weight. The aim of this research is to determine the relationship between Body Mass Index (BMI) and the shape of the longitudinal arcus pedis angle in medical students in Surabaya. An analytic observational method with a cross-sectional research design was used with a sample size of 53 students. The results of this study conclude that there is a significant relationship between Body Mass Index and the shape of the longitudinal curve of the pedis in students (p-value: 0.009). An increased BMI will cause the pedis angle to widen which will result in the feet becoming flatter, thus affecting the body's balance when standing for a long time. Strong legs are associated with a normal Body Mass Index.